Highly active phosphite gold(I) catalysts for intramolecular hydroalkoxylation, enyne cyclization and furanyne cyclization - Blanco Jaimes, Maria Camila; Rominger, Frank; Pereira, Mariette M.; Carrilho, Rui M. B.; Carabineiro, Sónia A. C.; Hashmi, A. Stephen K. (Chemical communications, 2014)
New and highly active mononuclear phosphite gold(I) catalysts are described. Turn-over numbers up to 37 000 for the furan-yne reaction and up to 28 000 000 for the two-fold hydroalkoxylation of alkynes are reported.
Gesehen am 13.10.2020